High polymerase ε expression associated with increased CD8+T cells improves survival in patients with non-small cell lung cancer. - Kyueng-Whan Min (PLoS ONE, 2020)
DNA replicase polymerase ε (POLE) is critical in proofreading and correcting errors of DNA replication. Low POLE expression plays a pivotal role in accumulation of mutations and onset of cancer, contributing to development and growth of tumor cells. The aim of this study is to reveal the survival, alternative genes and antitumoral immune activities in non-small cell lung cancer (NSCLC) patients with low POLE expression and provide treatment strategies that can increase their survival rates. This study investigated the clinicopathologic parameters, various tumor-infiltrating lymphocytes (TILs), endogenous retrovirus, molecular interactions and in vitro drug screen according to POLE mutation/expression in 168 and 1,019 NSCLC patients from the Konkuk University Medical Center (KUMC) and the Cancer Genome Atlas, respectively. We identified mutations of 75 genes in the sequencing panels, with POLE frame shift p.V1446fs being the most frequent (56.8%) in KUMC based on 170 targeted sequencing panels. Mutant and high expression of POLE correlated with favorable prognosis with increased TILs and tumor mutation burden, compared with wild type and low expression of POLE. We found specific molecular interactions associated with cell cycle and antigen presentation. An in vitro drug screen identified dasatinib that inhibited growth of the NSCLC cell line with low POLE expression. POLE could contribute to the future development of anticancer drugs for patients with NSCLC.